1995
DOI: 10.2527/1995.7372033x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chromium picolinate on growth, body composition, and tissue accretion in pigs

Abstract: An experiment was conducted to evaluate the effect of dietary chromium picolinate (CrP) on growth and body composition of pigs. Twenty-four barrows (three from each of eight litters) were randomly allotted within litter to one of three treatments: 1) basal (B) diet from 19.1 to 106.4 kg BW (Control); 2) B from 19.1 to 57.2 kg BW and then B + 200 ppb of chromium as CrP from 57.2 to 106.4 kg BW (CrP-F); and 3) B + 200 ppb of chromium as CrP from 19.1 to 106.4 kg BW (CrP- GF). Average daily gain and ADFI were red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
2
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 20 publications
7
46
2
5
Order By: Relevance
“…However, it was reported that dietary CrPic could increase heart weights of lambs (Kitchalong et al, 1993) and rats (Hasten et al, 1993). Weights of liver and kidney were also observed to be decreased in pigs fed CrPic (Boleman et al, 1995). The decrease in weight of spleen by addition of 450 ppb Cr from CrNano observed in this study indicated that supplemental Cr might have effect on immune system of rat.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…However, it was reported that dietary CrPic could increase heart weights of lambs (Kitchalong et al, 1993) and rats (Hasten et al, 1993). Weights of liver and kidney were also observed to be decreased in pigs fed CrPic (Boleman et al, 1995). The decrease in weight of spleen by addition of 450 ppb Cr from CrNano observed in this study indicated that supplemental Cr might have effect on immune system of rat.…”
Section: Discussionsupporting
confidence: 45%
“…This agrees with Lindemann et al(1995) who reported that supplemental Cr as CrPic improved FE in growing-finishing pigs. However, Amoikon et al(1995) and Boleman et al(1995) both reported that CrPic had no effect on FE in pigs. Sahin et al(2001) also found that addition of 200 and 400 ppb Cr from CrCl 3 had no effect on FE in growing rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos trabalhos efetuados com cromo para suínos em crescimento e terminação não apontam diferenças nessa característica quando se utiliza qualquer forma de cromo quelatado (BOLEMAN et al, 1995;CROMWELL, 1995CROMWELL, , 1999ALMEIDA et al, 2010).…”
Section: Resultsunclassified
“…que apresenta os mesmos níveis proteicos e aminoacídicos. Para a suplementação com 200ppb de picolinato de cromo, alguns trabalhos apontam aumento da área de olho de lombo (LINDEMANN et al, 1995;CROMWELL, 1997), entretanto, outros referem que esta característica não se altera com a inclusão deste mineral (BOLEMAN et al, 1995;CROMWELL, 1995CROMWELL, , 1999.…”
Section: Resultsunclassified
“…While a number of authors reported no or positive effects on those parameters, negative effects on weight gain of barrows, after supplementing the diet with as low as 0.2 mg Cr (from Cr-picolinate or Cr-propionate) kg -1 diet, were described in two studies (Boleman et al, 1995, Matthews et al, 2001). However, in crossbred pigs of each sex administered either a basal diet containing 2075 mg Cr kg -1 or a total of 5000 mg Cr kg -1 from different sources, and namely Cr-picolinate, Cr-propionate, Cr-methionine or Cr-yeast, for 75 days, average daily gain remained unaffected or even showed a limited but statistically significant increase (Cr-yeast, P < 0.025); among the tested serum clinical chemistry parameters, only K, CO 2 and alkaline phosphatase values were significantly different from the control values, with differences related to the source of Cr supplementation but within what is considered as a normal range for this species (Merck, 2005).…”
Section: Pigsmentioning
confidence: 99%